Evidence for an Early Origin of Vernalization Responsiveness in Temperate Pooideae Grasses . Issue 1 (29th July 2016) - McKeown, Meghan; Schubert, Marian; Marcussen, Thomas; Fjellheim, Siri; Preston, Jill C.
Abstract : Cold-regulated VRN1 and VRN3 expression is consistent with an early origin of vernalization responsiveness in the temperate Pooideae grasses. Abstract: The ability of plants to match their reproductive output with favorable environmental conditions has major consequences both for lifetime fitness and geographic patterns of diversity. In temperate ecosystems, some plant species have evolved the ability to use winter nonfreezing cold (vernalization) as a cue to ready them for spring flowering. However, it is unknown how important the evolution of vernalization responsiveness has been for the colonization and subsequent diversification of taxa within the northern and southern temperate zones. Grasses of subfamily Pooideae, including several important crops, such as wheat ( Triticum aestivum ), barley ( Hordeum vulgare ), and oats ( Avena sativa ), predominate in the northern temperate zone, and it is hypothesized that their radiation was facilitated by the early evolution of vernalization responsiveness. Predictions of this early origin hypothesis are that a response to vernalization is widespread within the subfamily and that the genetic basis of this trait is conserved. To test these predictions, we determined and reconstructed vernalization responsiveness across Pooideae and compared expression of wheat vernalization gene orthologs VERNALIZATION1 ( VRN1 ) and VRN3 in phylogenetically representative taxa under cold and control conditions. Our results demonstrate that vernalization responsive Pooideae species are widespread, suggesting that this trait evolved early in the lineage and that at least part of the vernalization gene network is conserved throughout the subfamily. These results are consistent with the hypothesis that the evolution of vernalization responsiveness was important for the initial transition of Pooideae out of the tropics and into the temperate zone.